2014
DOI: 10.1177/0957650914532267
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic and conjugate simulations on the flow field in a gas turbine vane with pressure side film cooling and trailing edge cutback

Abstract: The present study concentrates on the numerical investigation of pressure side film cooling in a linear nozzle vane cascade typical of a high-pressure turbine in gas turbine engines. The cooling scheme features a pressure side cutback and two rows of cooling holes located upstream of the cutback. The main goal is to evaluate the applicability of a simple numerical method, i.e. the steady incompressible Reynolds-averaged Navier Stokes, in such a complex industrial application. The simulations are performed acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…9b and 10a) can be explained by considering that, as stated before, TLC measurements were performed on a model manufactured with a rapid prototyping machine while PSP measurements were run on a Plexiglas model. The unavoidable imperfections in the internal geometry and the high roughness of the internal surface of the first model caused a flow separation in the slot exit section at low injection rates, as documented in Ravelli and Barigozzi [26]. This separation was not present in the Plexiglas models, realized by a 4 axis NC machine assuring a precise geometry definition with very smooth internal surfaces.…”
Section: Mfr (%) Br Row#1 Br Row#2 Br Slotmentioning
confidence: 90%
See 1 more Smart Citation
“…9b and 10a) can be explained by considering that, as stated before, TLC measurements were performed on a model manufactured with a rapid prototyping machine while PSP measurements were run on a Plexiglas model. The unavoidable imperfections in the internal geometry and the high roughness of the internal surface of the first model caused a flow separation in the slot exit section at low injection rates, as documented in Ravelli and Barigozzi [26]. This separation was not present in the Plexiglas models, realized by a 4 axis NC machine assuring a precise geometry definition with very smooth internal surfaces.…”
Section: Mfr (%) Br Row#1 Br Row#2 Br Slotmentioning
confidence: 90%
“…To fully assess the binary PSP technique, the same methodology successfully tested on the flat plate case was applied to a more complex geometry like the cooling of the pressure side of a high pressure nozzle vane cascade equipped with a cutback trailing edge. This test case was chosen because the same geometry has been extensively tested, both experimentally [22][23][24] and numerically [25,26], at Bergamo University Laboratory so film cooling effectiveness distributions measured at variable MFR and downstream Mach number with the wide banded TLC technique are available for comparison [22]. These tests were considered by the authors very challenging.…”
Section: The Vane Cascade Test Casementioning
confidence: 99%
“…By solving steady three-dimensional RANS equations, the computational results of the endwall heat transfer were found to have a good agreement with experimental data. 15 Ravelli and Barigozzi 16 studied the conjugate heat transfer characteristic with a vane pressure side cooling scheme. They reported that the heat transfer coefficient could be predicted reasonably by both adiabatic and conjugate approaches.…”
Section: Introductionmentioning
confidence: 99%